The Implementation of Gerakan Literasi Sekolah (Gls) as a Technique for Teaching Reading - Farida Nova Kurniawati (Essence: Journal of English Language Teaching, Linguistics, and Literature, 2024)
Students’ reading habit in Indonesia is still low. Gerakan Literasi Sekolah (GLS) is created by the government to solve this problem. Reading non-learning book in 15 minutes before the lesson begun is one of activities in this movement. Observation, interview, students’ response journal, field note, and video recording were done for data collection to investigate the implementation of GLS in one of state Islamic junior high school in a small city in East Java to find out students’ negotiation to a text for their reading comprehension and to know that the implementation of GLS is effective or not for teaching reading. The result of this descriptive qualitative research shows that the school is in habituation implementation stage of GLS. The students use both of bottom-up and top-down process to negotiate with a text for their reading comprehension. This research also proves that the implementation of GLS is effective as a technique for teaching reading. Keywords: GLS, Teaching Reading, Teaching Technique